CAPACITY BUILDING OF COMMUNITY-BASED REHABILITATION TO ACCESSIBILITY OF PERSONS WITH DISABILITIES - Annisa - Fathin; R Ekeu Agiati; Neni Kusumawardhani (Lembaga Penelitian Universitas Pasundan, 2018)
Capacity building is the capability enhancement process of the Community-Based Rehabilitation (RBM) caretaker in providing services to persons with disabilities, so they could access their needed services. The purpose of this research is to study Capacity Building of Community-Based Rehabilitation to Accessibility of Persons with Disabilities in Cibiru Wetan Village, Cileunyi Sub-district, Bandung Regency. The research method used is qualitative with action research design. Data source used is primary data source and secondary data source. The data collection techniques used were in-depth interviews, participant observation, documentation study, and Focus Group Discussion (FGD). Data validity checking technique used is credibility, transferability, dependability, and confirmability. Furthermore, the results of this study were analyzed by qualitative analysis techniques. The results showed that the capacity building of RBM Cibiru Wetan caretaker enhances the capability of RBM caretaker to provide services to persons with disabilities.Shown by RBM Cibiru Wetan caretaker in providing services to identify the needs and problem of persons with disabilities, assessment, planning and working matrix, improving the RBM management, as well as recording the handling of cases of persons with disabilities. The RBM caretaker capacity impacts the quality of RBM services to be comprehensive and based on social work.